OPTIMAL DESIGN ANALYSIS OF PCTFE SEAT STRUCTURE OF ULTRA-LOW TEMPERATURE BALL VALVE BASED ON RESPONSE SURFACE METHOD (MT) - ZHANG XiHeng; YU RongFang; ZHANG Chi; ZHOU Yi; SUN ShuaiJun (Jixie qiangdu)
To optimize the structural strength of the soft-sealing ball valve seat at ultra-low temperature, a design method combining response surface method and genetic algorithm was proposed, which took the maximum equivalent stress as the optimization objective. The stress-strain relationship of PCTFE, the material of low-temperature ball valve seat, under different working conditions was studied, and the tensile strength is the only important basis to judge the strength of PCTFE. The central combination design method was adopted, established the response surface model of stress on structural parameters, analyzed the interaction between parameters. The optimal structural parameters of valve seat were obtained based on response face combined with genetic algorithm. The results show that the maximum equivalent stress of valve seat decreases with the increase of valve seat thickness and inner and outer diameter of valve seat sealing face. The inner diameter of sealing face of valve seat has the most significant effect on the maximum equivalent stress.